Periodontal status of mandibular second molar after extraction of impacted mandibular third molars- a prospective clinical trial - Swathi Singh; Naga Venkata Satya Sai Sruthima Gottumukkala; Santosh Venkata Ramesh Konathala; Subhadra Gautami Penmetsa; Dwarakanath Chinniswami Doraisami; Vivek Bypalli (European Oral Research)
Mandibular third molar (M3) extraction is the common surgical procedures carried out; however, one of the complications is development of periodontal disease in adjacent second molars (M2). Hence the purpose of this study was to evaluate the effect of extraction of M3 on the periodontal status of M2. Materials and Methods Study included 120 sites with mandibular M2 adjacent to the impacted M3. Plaque index(PI), gingival index(GI), probing pocket depths(PD), clinical attachment levels(CAL), Gingival recession(GR) and alveolar bone height(ABH) before and 9-12 months after surgical extraction of M3 were assessed. Patients perception was assessed using dichotomous rating. Four types of impactions(IMP) were included along with surgical cofactors like degree of impaction, flap design, bone removal, tooth sectioning. Results At baseline mesioangular and horizontal IMP showed greater PPD and CAL. After extraction of M3 there was significant decrease in PPD & CAL. 14% cases showed significant increase gingival recession at the distobuccal of M2. Although 10.9% of patients had an alveolar bony defect(ABD) distal to the M2, there was considerable improvement in ABH from baseline. The ABDs are mostly associated with mesioangular and horizontal IMP. Conclusion Extraction of impacted M3 proves to be beneficial on periodontal status of M2. However, occasionally, mesioangular and horizontal IMP are likely to develop ABD distal to M2 and hence can be followed by regenerative procedures to prevent the formation of ABD.